Taxonomy of the genus Cyrtogrammomma Pocock, 1895 (Araneae, Mygalomorphae, Theraphosidae) with a description of a new species from Brazil - Gonzalez-Filho, Hector Manuel Osorio [UNESP]; Fonseca-Ferreira, Rafael [UNESP]; Brescovit, Antonio Domingos; Guadanucci, José Paulo Leite [UNESP] (Pensoft Publishers, 2022)
The genus Cyrtogrammomma Pocock, 1895 was proposed based on specimen samples from Monte Roraima, Guyana, and allocated in the family Barychelidae. However, the most recent cladistic analysis transferred Cyrtogrammomma to Theraphosidae. Herein, we amended the diagnosis and description of C. monticola, providing a redescription of the male, and new illustrations, including the description of a new cuticular structure consisting of thick and stiff setae on dorsal metatarsi I and II of females. Moreover, we diagnose, describe and illustrate a new species of Cyrtogrammomma from northeastern Brazil: C. frevo sp. nov. In addition, we provide an identification key, new distribution records of the genus in the states of Alagoas, Bahia, Pará, and Pernambuco, in Brazil, and the first record for the genus in caves.
Keywords: 1888; Atlantic forest; Barychelidae; First record; Trichopelma simon